Introduction to radar analysis - Mahafza, Bassem R. (CRC Press, Taylor & Francis Group, 2018)
Introduction to Radar Analysis, Second Edition is a major revision of the popular textbook. It is written within the context of communication theory as well as the theory of signals and noise. By emphasizing principles and fundamentals, the textbook serves as a vital source for students and engineers. Many new exercise are included and the author provides comprehensive easy-to-follow mathematical derivations of all key equations and formulas.